Radiographic Differentiation of Tibiofemoral Joint Space Width in Kellgren–Lawrence Grade 2 and 3 Osteoarthritis in Malang - Irma Darinafitri; Suaydiy Okdiyanzah (Asian Journal of Health Research, 2026)
Introduction: Osteoarthritis (OA) is a leading cause of disability worldwide. Although the Kellgren–Lawrence (KL) grading system is widely used, it remains subjective. Quantitative fixed joint space width (fJSW) offers a more objective assessment of structural severity, and is particularly relevant in populations such as Javanese communities, where habitual squatting may influence knee joint loading patterns, making evaluation in Malang, East Java, of specific interest. Material and Methods: This study analyzed 111 knees (KL grade 2 or 3) at Saiful Anwar Hospital in 2024. Medial and lateral fJSW were measured on standardized weight-bearing radiographs using a perpendicular subchondral technique. Results: The participants were predominantly female (69.86%) and aged 40-60 years (47.95 %). KL grade 2 was more frequent than grade 3 (56.76% vs. 43.24%), with more bilateral involvement observed (52.05%). Mean medial fJSW are 3.55 ± 1.72 mm in KL 2 and 3.12 ± 1.89 mm in KL 3, while mean lateral fJSW are  4.47 ± 1.26 mm in KL 2 and 5.15 ± 2.27 mm in KL 3. An optimal medial cutoff of 5.03 mm demonstrated high sensitivity (93.8%) but low specificity (25.4%) for disease staging. Despite limited specificity, this threshold may be useful as a screening tool to reduce underdiagnosis of KL grade 3 osteoarthritis by prioritizing sensitivity in detecting more advanced disease. Conclusion: Findings confirm a pattern of medial narrowing and lateral preservation characteristic of varus-driven attrition. However, the low specificity of fJSW suggests that quantitative narrowing alone is insufficient for grading; it must be integrated with other structural domains, such as osteophyte formation, to differentiate KL2 from KL3.